Statistical Modeling of Live Body Weight and Linear Body Measurements of Local Chicken at Different Agro-Ecologies of Ethiopia - Bekele , Berhanu; Melesse, Aberra; Esatu, Wondmeneh; Dessie, Tadelle (International Journal of Poultry Science, 2021)
Objective: This study was conducted to determine the relationship between live body weight and linear body measurements and to establish a model for predicting body weight using linear body parameters of the indigenous chickens of Ethiopia. Materials and Methods: A total of 520 adult chickens (130 males and 390 females) were randomized from three agro-ecologies (120 from lowland, 200 from midland and 200 from highland). Body parameters including beak length, body length, breast circumference, comb length, ear lobe length, shank circumference, shank length, wattle length and wingspan were measured using flexible measuring tape. Data were analyzed using SAS and SPSS. Results: Agro-ecology had significant effect (p<0.05) on body length, live body weight, breast circumference, shank circumference, shank length and wingspan. In indigenous chickens, the strong, positive and significant (p<0.05) correlation of body weight with breast circumference, body length and shank length indicate that, these variables could provide a good estimate in predicting body weight of chicken. Body length, chest circumference and shank length showed highest R2 (0.599, 0.517 and 0.382), respectively. This indicates that 59.9, 51.7 and 38.2% of body weight variation in indigenous chicken of Ethiopia depends on body length, breast circumference and shank length, respectively. Equivalently, linear measurements with highest R2 imply that they could be the best predictors of body weight of indigenous chickens in Ethiopia. Live body weight had significant (p<0.05) association with the linear body measurements; body length, chest circumference, shank length and wingspan to which the model has been subjected. Therefore, multiple linear regression model relating body weight and linear body measurements of Ethiopian indigenous chicken is Ŷ = -0.949+0.039BoL+0.037SL+0.026BC+0.006WS. Conclusion: Body length, shank length and breast circumference can be used to predict body weight of Ethiopian indigenous chicken compared to the other linear body measurements.